Effects of Gross Domestic Product of Textile and Textile Product to Reserve for Foreign Exchange and Labor Absorption of Textile and Product Textile - Heru Subiyantoro; Usmansyah Usmansyah (Journal Research of Social Science, Economics, and Management, 2023)
The textile and textile products industry have an important role in the country's economy. In various data it is revealed that the contribution of the textile and textile products industry to Gross Domestic Product is significant, which in turn will have an impact on the State's Foreign Exchange Reserves. On the other hand, this industry also usually deploys a large workforce, so it can be said that the growth of this industry will affect the number of workers absorbed. This study aims to determine and analyze the effect of the Gross Domestic Product (GDP) of the Textile and Textile Products Industry in 12 countries in the period 2012 – 2021 and analyze its effects on Foreign Exchange Reserves and Labor Absorption. This study uses ECM panel data regression with the integration order level of Third Difference. The results of the study show that the GDP of TTP has a significant effect on the Foreign Exchange Reserves and the Absorption of TTP Labor with a unidirectional relationship.